2003
DOI: 10.1093/bja/aeg162
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental oxygen for prevention of nausea and vomiting after breast surgery

Abstract: The incidence of vomiting decreased during the short postoperative administration of supplemental oxygen 50%. However, perioperative oxygen 50% administration did not prevent PONV over the 24-h follow-up period in patients undergoing breast surgery performed under general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 8 publications
1
33
0
2
Order By: Relevance
“…These later studies may be limited by sub-therapeutic levels of supplemental oxygen. 5 Our study adds further to this evidence and clearly demonstrates that supplemental intraoperative 80% oxygen, compared with routine intraoperative 30% oxygen, does not reduce the incidence of PONV during the initial 24-hr period among women undergoing laparoscopic gynecological surgery. No benefit was observed in any ''subgroup'' time periods, including immediately following surgery in the PACU (pre-discharge), time after discharge from hospital (post-discharge), early PONV (0-6 hr), or late PONV ([6-24 hr).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…These later studies may be limited by sub-therapeutic levels of supplemental oxygen. 5 Our study adds further to this evidence and clearly demonstrates that supplemental intraoperative 80% oxygen, compared with routine intraoperative 30% oxygen, does not reduce the incidence of PONV during the initial 24-hr period among women undergoing laparoscopic gynecological surgery. No benefit was observed in any ''subgroup'' time periods, including immediately following surgery in the PACU (pre-discharge), time after discharge from hospital (post-discharge), early PONV (0-6 hr), or late PONV ([6-24 hr).…”
Section: Discussionmentioning
confidence: 52%
“…4 Later studies in subjects undergoing breast surgery, ambulatory gynecologic laparoscopy, thyroidectomy, laparoscopic cholecystectomy strabismus, or dental surgery failed to demonstrate any benefit from supplemental intraoperative oxygen on PONV. [5][6][7][8][9][10][11] A recent meta-analysis of 1729 patients from ten studies has been published (since the conduct of this trial but prior to this current study publication) synthesizing the data from the aforementioned studies. Regardless of the type of surgery, the meta-analysis did not demonstrate any overall effect from supplemental intraoperative oxygen on PONV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purhonen's group [8] investigated influence of FIO 2 of 0.5 in breast surgery and did not find the difference in PONV compared with FIO 2 of 0.3, 89% vs. 82%, at 24 hours, but the incidence of POV at 2 hours was significantly different, 0% vs. 12%, respectively. In the current study only FIO 2 of 0.8 decreased the incidence of early POV compared with FIO 2 of 0.3 ( Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…FIO 2 of 0.5 is more commonly used in anesthesia practice when higher FIO 2 is desirable. One study found no effect of FIO 2 of 0.5 on PONV in patients undergoing breast surgery but suggested beneficial effect on early postoperative vomiting [8].…”
Section: Introductionmentioning
confidence: 99%